210Po in popular medicinal herbs from Poland. Issue 3 (4th May 2019) - Boryło, Alicja; Romańczyk, Grzegorz; Kaczor, Marcin; Skwarzec, Bogdan
ABSTRACT: Herbs are an important part of traditional medicine in Poland. Therefore, the aim of this study was the determination of polonium 210 Po in 48 selected medicinal herb samples from the Polish market. The activity concentrations of 210 Po were measured using alpha spectrometry. The activity concentration of 210 Po was in the range from 0.3 ± 0.1 to 28.2 ± 0.4 Bq kg –1 . The obtained results were compared with corresponding studies conducted worldwide. A higher 210 Po activity concentration was observed in the above-ground part of plants. The obtained results show that the highest 210 Po activity concentration was observed in evergreen plants and winter-hardy plants. Yet even infusions with 2 g of the most contaminated herbs examined were considered to be radiologically safe.